ثورة الزَّنج وتداعياتها السياسية على الدولة العباسية خلال الفترة (255-270هـ/869-833م) (Comprehensive Journal of Science, 2025)
The Zanj Rebellion is considered one of the most dangerous uprisings that took place against the Abbasid state, lasting for more than fourteen years. It was led by ʿAlī ibn Muḥammad, who claimed prophethood and knowledge of the unseen. He migrated to Bahrain to spread his message, then moved from one region to another until he reached Basra, where he gained the loyalty of the Zanj laborers working in the salt marshes. He spread his ideas among them, and a large number followed him, which earned him the title “Leader of the Zanj.” With these oppressed groups, he built a powerful force through which he controlled Basra and its surrounding areas, and he established the city of al-Mukhtāra to serve as the center and headquarters of his movement.When Abu Ahmad al-Muwaffaq assumed leadership of the Abbasid armies by order of his brother, Caliph al-Muʿtamid, he was able—thanks to his strength and determination—to fight the leader of the Zanj in fierce battles that eventually ended with the latter’s death at the hands of Abu Ahmad al-Muwaffaq. Thus, he succeeded in suppressing the rebellion in the year 270 AH / 884 AD.